PILIHAN DIKSI DALAM PRODUCT PLACEMENT DALAM SINETRON TUKANG OJEK PENGKOLAN - rosmiati, ana (Institut Seni Indoensia Surakarta, 2021)
This research on the accuracy of diction in the placement of product placement in the soap opera Tukang Ojek Pengkolan (TOP) at the RCTI Television Station is interesting considering that there are advertising products that are inserted when the soap opera is running. Product placement has become a trend to be shown in soap operas and films in Indonesia with the aim of introducing products effectively because at the same time as the broadcast time, TOP soap operas are one of the soap operas that air on RCTI with high viewership ratings. The story in this soap opera is relatively light about the life of a motorcycle taxi driver. The problem in this research is how to choose an effective diction placement in the product placement of the soap opera Tukang Ojek Pengkolan and how to place the product placement in the soap opera Tukang Ojek Pangkalan when viewed from the nature of the advertisement. The purpose of this study was to find an effective choice of diction placement in the product placement of the soap opera Tukang Ojek Pengkolan and to describe the advertising nature of the product placement found in the soap opera Tukang Ojek Pengkolan. This type of research is a qualitative descriptive research. The data source in this study is the primary data source in the form of the soap opera Tukang Ojek Pengkolan (TOP).Keywords : Product placement, advertisement, soap opera TOP